2019
DOI: 10.4236/jbm.2019.712014
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Preventive Treatment in Pregnancy with Sulphadoxine-Pyrimethamine Does Not Have Effect on Maternal Hemoglobin at Delivery and Birth Weight in Kisangani, Democratic Republic of Congo

Abstract: Background: The consequences of malaria during pregnancy are different regarding local conditions of malaria transmission. In stable malaria areas, the main complications are maternal anaemia and fetal growth restriction. This study aims to determine if pregnancy-associated malaria is associated with the risk of the above-mentioned complications and to determine if IPTp-sp reduces them in Kisangani. Methods: It is a cross-sectional analytical study conducted in parturients, in 6 medical facilities of Kisangani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18] Indeed, Losimba et al 19 reported that high resistance to sulfadoxine-pyrimethamine could make intermittent preventive treatment during pregnancy using sulfadoxinepyrimethamine less effective in preventing low birth weight. This was confirmed by Labama et al 20 who found no benefits of intermittent preventive treatment during pregnancy using sulfadoxinepyrimethamine in preventing low birth weight in Kisangani where the current study was conducted.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18] Indeed, Losimba et al 19 reported that high resistance to sulfadoxine-pyrimethamine could make intermittent preventive treatment during pregnancy using sulfadoxinepyrimethamine less effective in preventing low birth weight. This was confirmed by Labama et al 20 who found no benefits of intermittent preventive treatment during pregnancy using sulfadoxinepyrimethamine in preventing low birth weight in Kisangani where the current study was conducted.…”
Section: Discussionsupporting
confidence: 86%
“…19 Indeed, it has been previously reported that sulfadoxine-pyrimethamine has failed to prevent low birth weight in Kisangani. 20 The resistance to sulfadoxine-pyrimethamine raised serious concerns regarding its use for the intermittent preventive treatment during pregnancy. 21 Therefore, alternative options such as prophylaxis using mefloquine, sulfadoxine-pyrimethamine plus azithromycin or artesunate, chloroquine, sulfadoxine-pyrimethamine plus chloroquine have been proposed.…”
Section: Introductionmentioning
confidence: 99%